Fuegian Firestone Quarry: Iron Pyrite on Capitan Aracena Island, Magallanes Archipelago, Southern Chile - Gallardo, Francisco; Ballester, Benjamin; Prieto, Alfredo; Sepulveda, Marcela; Gibbons, Jaime; Gutierrez, Sebastian; Carcamo, Jose (My University, 2018)
Fire was essential for the ancient inhabitants of Tierra del Fuego, at the southernmost end of the Americas. The Fuegians, as these human groups are traditionally known, produced fire primarily by striking a piece of iron pyrite against a flint nodule. Several European chroniclers mention this firestone technology and note its social value, a conclusion based on the fact that it was carefully safeguarded in leather pouches. Anglican missionary Thomas Bridges visited one of these pyrite sources in 1883 with two Yaghan guides and left behind a brief description of its out-of-the-way location. Almost 130 years later, we rediscovered this mine on Capitan Aracena Island in the Strait of Magellan. In this study, we present a brief report focused on the mine's exact location, archaeological materials, and layout, and we offer the first physical-chemical description of the pyrite source. Comparison of these results to similar analyses of archaeological samples from the Santa Isabel Island settlements in the Magellan Strait suggests that the early inhabitants of the area used different pyrite sources, only one of them corresponding to the Capitan Aracena Island mine.
Keywords: Archipelago; Human settlement